Heat transfer and pressure drop characteristics of water flow boiling in open microchannels. (July 2019) - Yin, Liaofei; Jiang, Peixue; Xu, Ruina; Hu, Haowei; Jia, Li
Highlights: DI water flow boiling in open microchannels was studied experimentally. Onset of stratified flow meant an alternation of dominant heat transfer mechanism. Effects of operating conditions on heat transfer mainly worked in stratified flow. The two phase stratification inhibited the continued increase of pressure drop. Abstract: The open microchannel configuration can mitigate several drawbacks of closed microchannel for flow boiling heat transfer, but the studies related to flow boiling in open microchannels are limited up to now. In this study, experiments were conducted to investigate the heat transfer and pressure drop characteristics during flow boiling of deionized water (DI water) in open microchannels and to analyze the effects of operating conditions and channel dimensions. The experiments were carried out with the inlet subcooling Δ T sub  = 20, 35, 50 °C at different mass fluxes ranging from 174 to 374 kg/m 2  s for varied applied heat flux 214.9–1355.1 W/cm 2 . Two open microchannel samples with different geometry dimensions were tested. High speed flow visualizations were realized to illustrate the flow pattern transitions during flow boiling in open microchannels. Experimental results showed that the onset of stratified flow (OSF) denoted an alternation of dominant heat transfer mechanism at which the heat transfer coefficient (HTC) was largest during the flow boiling. The effects of operating conditions and channel dimensions on the HTC and two-phase pressure drop in open microchannels were mainly observed in the stratified flow regimes, during which nucleate boiling and convective evaporation jointly controlled the flow boiling process. In addition, the open microchannel with smaller size but a great number of channels had a better heat dissipation capability along with a higher pressure drop in stratified flow regimes.